Analysis of Malaria Disease Classification Based on Age in the Work Area of Idanogawo Health Center, Idanogawo District, Nias Regency Using the Decision Tree Algorithm - Sipra Barutu (SEAN Institute, 2024)
Malaria is an infectious disease caused by the Plasmodium parasite, which is transmitted through the bite of the Anopheles mosquito. This disease can affect individuals of all age groups, but its prevalence varies between age groups. This study aims to analyze the relationship between age and malaria incidence in the working area of ​​the Idanogawo Health Center, Nias Regency, using the Decision Tree algorithm. Secondary data collected from medical records at the Idanogawo Health Center were processed through preprocessing to obtain age and malaria incidence attributes. The results of the analysis showed that the age group <30 years had the highest percentage of malaria incidence (80%), followed by the age groups 30-39 years and 40-49 years, each of which recorded an incidence rate of around 73%. The age group >=50 years also showed a high incidence of malaria (100%), although the sample size was small. These findings indicate that malaria attacks younger people more, but older age groups are also significantly affected.